Nontuberculous Mycobacterial Infections After Silicone Breast Implant Reconstruction Emphasize a Diversity of Infecting Mycobacteria. (2nd September 2017) - Romero, Fabian A; Powell, Eleanor A; Babady, N Esther; Kaltsas, Anna; Figueroa, Cesar J; Pulitzer, Melissa; Mehrara, Babak J; Glickman, Michael S; Morjaria, Sejal
Abstract: Postsurgical skin and soft tissue infections (SSTIs) caused by nontuberculous mycobacteria (NTM) are uncommon, indolent, difficult to treat, and often mimic pyogenic bacterial infections. Here we present 3 cases of NTM infections following placement of silicone implants for reconstructive breast surgery. These cases emphasize the importance of a high index of suspicion for NTM in patients with SSI after a prosthetic reconstruction refractory to conventional antibiotic therapy and the importance of early investigation with mycobacterial-specific diagnostics.